Application of Molecular Methods for Carbapenemase Detection - Bilozor, Anastasia; Balode, Arta; Chakhunashvili, Giorgi; Chumachenko, Tetyana; Egorova, Svetlana; Ivanova, Marina; Kaftyreva, Liidia; Kõljalg, Siiri; Kõressaar, Triinu; Lysenko, Olga; Miciuleviciene, Jolanta; Mändar, Reet; et al. (Frontiers in Microbiology, 2019)
This study has evaluated the correlation between different carbapenemases detection methods on carbapenem non-susceptible Klebsiella pneumoniae strains from Northern and Eastern Europe; 31 institutions in 9 countries participated in the research project, namely Finland, Estonia, Latvia, Lithuania, Russia, St. Petersburg, Poland, Belarus, Ukraine and Georgia. During the research program, a total of 5,001 clinical K. pneumoniae isolates were screened for any carbapenem non-susceptibility by the disk diffusion method, Vitek 2 or Phoenix system following the EUCAST guideline on detection of resistance mechanisms, version 1.0. Strains isolated from outpatients and hospitalized patients from April 2015 to June 2015 were included. All types of samples (blood, pus, urine, etc.) excluding fecal screening or fecal colonization samples have been represented. In total, 171 carbapenemase screening-positive K. pneumoniae isolates (3.42%) were found and characterized. Several methods were used for detection of carbapenemases production, including Luminex assay (PCR and hybridization), whole genome sequencing, MALDI-TOF based Imipenem degradation assay, and immunochromatography testing. Minimal inhibitory concentration determination for Meropenem by agar-based gradient method was also used. Finally, 83 K. pneumoniae strains were carbapenemase negative by all confirmation methods (49.4% of all screening-positive ones), 74 - positive by 3 methods (44.0%), 8 - positive by 2 methods (4.8%) and 3 - positive by only one method (1.8%). The sensitivity of the tests was 96.3% for WGS and MALDI-TOF assay (both 3 undetected cases), and 95.1% for Luminex-Carba (4 undetected cases). The most commonly detected carbapenemases were NDM (n=54) and OXA-48 (n=26), followed by KPC-2, VIM-5 and OXA-72 (one case of each). Our results showed that different types of carbapenemases can be detected in the countries involved in the project. The sensitivity of our methods for carbapenemase detection (including screening as a first step and further confirmation tests) was >95%, but we would recommend using different methods to increase the sensitivity of detection and make it more precise.